PERBEDAAN EFEKTIVITAS METODE TERAPI MUSIK RELIGI DENGAN MASSAGE EFFLEURAGE TERHADAP NYERI PERSALINAN KALA I FASE AKTIF PRIMIGRAVIDA - Sri Wulan; Novita Br Ginting Munthe (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Pain is an unpleasant condition that is part of childbirth caused by physical or emotional stimulation. Labor pain management is needed to break the pain loop with all the consequences caused. Treatment of non-pharmacological pain is more selected because it is cheaper, safer, and can be done by maternity mothers or families such as religious music therapy and Effleurage Massage. This research aims to determine the difference in effectiveness of religious music therapy method with Massage Effleurage against maternity pain when I active phase Primigravida. This research is a Quasi-experiment with Pre and Post Test With Non Control Design, comparing two observations, namely Pre and Post Test of religious music therapy Group and Massage Effleurage Group. The instrument used is the Numeric Rating scale (NRS) scale observation sheet 0-10. The population in this study was a normal maternity mother who was in RS GrandMed Lubuk Pakam. Sampling using Probability Sampling technique with a sample amount of 36 people. The results of data analysis by using Independent T Test test showed the value of P value 0.02 < 0.05 which means there is a significant distinction between giving methods of religious music therapy with massage effleurage. Recommended to maternity mothers in order to apply the therapy for religious music and massage effleurage because both methods are effectively used to reduce labor pains